A non-covalent cation-π interaction-based humidity-driven electric nanogenerator prepared with salt decorated wrinkled graphene. (August 2019) - Zhen, Zhen; Li, Zechen; Zhao, Xuanliang; Zhong, Yujia; Huang, Meirong; Zhu, Hongwei
Abstract: Strong non-covalent cation-π interactions were discovered about three decades ago. However, the application of such interfacial behavior on carbon nanomaterials has been investigated only in recent years. In particular, with the increasing interests in graphene, efforts have been made to promote the energy generation through macroscopically shifts of the liquid/solid boundary over the carbon surface, yet the effective ways to avoid the physical wearing caused by the macroscopically shifts still lack. In the present work, a high-efficiency humidity driven electric nanogenerator based on the interfacial cation-π interaction was reported. The generator was prepared using the wrinkled graphene with intentionally increased defects and uniformly distributed wrinkles for ultrafast water evaporation, preventing excessive water accumulation and deposition of well-distributed salt crystals. Electricity was generated by manipulating the formation of ionic liquid microdroplets on the graphene surface via water adsorption and desorption of salt crystals as the humidity varied. Our work provided a new strategy for the application of strong cation−π interactions, such as energy generation, gas sensing and biointerface for cell stimulation, with readily achievable stimuli, high stability, comparable efficiency and long lifetime. Graphical abstract: A high efficiency humidity driven electric nanogenerator based on the interfacial cation-π interaction is designed and prepared using the wrinkled graphene by preventing excessive water accumulation and deposition of well-distributed salt crystals. Electricity is generated by manipulating the formation of ionic liquid microdroplets on the graphene surface via the water adsorption and desorption of salt crystals as the humidity varies.Image 1 Highlights: A cation-π interaction utilization strategy is developed with a graphene-based humidity driven nanogenerator. The hydrophobic surface of graphene can accelerate the evaporation while preventing the aggregation of water droplets. Electricity is generated by manipulating the formation of ionic liquid microdroplets as the humidity varies.